Section 41 of the Road Transport Act 1987: a critical observation / Airol Irwan Limin, Ahmad Ghazali Muhamad Nadzri and Amalina Zainal Mokhtar. - Limin, Airol Irwan; Muhamad Nadzri, Ahmad Ghazali; Mokhtar, Amalina Zainal (2007)
This research is a detailed observation of the provision in the Road Traffic Act, 1987 in relation to causing death by reckless or dangerous driving i.e. Section 41. In doing this research, we sought to discover whether the punishment provided in Section 41 of the Road Transport Act 1987 is adequate to deter the public from driving recklessly or dangerously. Parliament had provided sufficient punishment within the section for this purpose. However, we had discovered that when the section had to be implemented and interpreted by the judges, the judges refrained from imposing the maximum sentence that had been provided. Upon an analysis of the judgments of the several cases that we identified, we observed that in the process of coming to their decisions, the judges took into account several factors surrounding both the offender and the accident itself. Amongst other things, the judges distinguished the two categories of reckless driving which included accidents that had arisen through momentary inattention and selfish disregard for the safety of the other. The judges also took into consideration the aggravating and mitigating factors which related to the offender itself. Based on the research that we have done, we propose several ideas and recommendations such as the judiciary should set up an independent advisory body to aid judges in deciding on the appropriate sentence. The executives should introduce a new syllabus in schools to educate to the public about the section itself. The media should also give some awareness to the public through advertisements, television programmes and national news. Legislative should also review the act from time to time to be in line with current situation. In all, we found out Section 41 is effective and in our opinion, we agree that Section 41 of the Road Transport Act 1987 basically provides sufficient punishment to the offender.